Spectrum of Thyroid Dysfunctions in Metabolic Syndrome in a Tertiary Care Hospital of Karachi, Pakistan - Darshan Kumar, Zunaira Nawaz, Rabiah Zaid, Syed Muhmmad Kashif, Ammara Abdul Majeed, Rashid Qadeer (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency and spectrum of thyroid dysfunction in patients with metabolic syndrome. Study design: Observational and descriptive study Place and duration of Study: Department of Medicine, Dr. Ruth Kum Pafu Civil Hospital Karachi from 1st January 2020 to 31st December 2020. Methodology: Four hundred and sixty eight patients were enrolled. Every patient was thoroughly examined and anthropometric measurement done (height, weight, waist circumference) and body mass index was calculated. Fasting blood samples were collected to measure fasting blood glucose, lipid profile and thyroid profile (Thyroid stimulating hormone, Free T4 and Free T3). Results: There were 186 (39.65%) males and 282 (60.34%) females. Patients aged between 30 to 69 years mean age was 48 years, mean BMI was 30.07. Thyroid profile including TSH, FT3, FT4 were normal in 246 (52.58%) patients, hyperthyroidism in 48 (10.34%) patients, subclinical hypothyroidism in 105 (22.41 %) and hypothyroidism in 69 (14.65%) patients. Results suggest positive correlation between BMI, TG, and thyroid profile while negative correlation between HDL cholesterol and thyroid profile. Conclusion: The positive correlation between thyroid dysfunction and metabolic syndrome. So it is suggested that patients with metabolic syndrome may require a thyroid profile which results in early detection of disease and timely treatment. Keywords: Thyroid dysfunction, Body mass index, Metabolic syndrome, Hypothyroidism, hyperthyroidism